Trust factors in the adoption of national electronic health records - Meira, Bruno (2013)
In the area of health, the Electronic Health Record (EHR) is increasingly seen as essential not only to ensure interoperability between systems, but also to assume the patient as the central entity of the health information. The success of the EHR depends on several factors of diverse nature, such as technical, ethical, legal, security and privacy. In the case of the adoption of new technology, an additional and particularly important class of factors is the one related to trust. The different entities that handle health information (doctors, patients, managers, etc.) have different needs and goals for the EHR and, therefore, evaluate their individual trust based on different factors. Assuming that the trust placed in the EHR by its main stakeholders is a relevant factor in its success, a set of factors influencing trust were identified and classified through a field study. The target of analysis was the Portuguese EHR initiative.